Connecting Neuroscience Principles and Education People Profile of Culture and Leadership: A Labour Market Approach - Lopes, Albino Anjos; Barrosa, Luis; Romana, Fernando Acabado; Martins, António Eduardo (Archives of Business Research, 2023)
Neurosciences, based on the founding idea of “neuroplasticity”, have helped to clarify the issue of initial (and integral) training of individuals based on the balanced structuring of the respective brain system. From what has been said, we would say that initial parental education, in times of an increasingly urban life (where parents delegate the education of children to school) does not seem to facilitate this balance of integrated development. It is important to discuss the connection between the neurosciences and education, concluding that this joint approach would be essential to guide quality levels and the researchers admit that the applicability of neuroscience research, for the improvement of pedagogy, has been, paradoxically, very limited. In general, we can define organizational culture as a set of beliefs, values and norms that influence the climate of a company, aligning employee behaviour and the strategic way in which the company positions itself in the market. Organizational culture is the essence of an organization. The supportive culture or clan culture presents a pleasant work environment, with a united organization that endures through loyalty and traditions, where interpersonal relationships are created, success is defended by teamwork, participation and consensus between employees and the organization. Leaders are considered mentors and there is a high level of commitment. In accordance with the updated works of Miranda, which seeks to reconcile the previous author and the OCAI model of R. Quinn and collaborators, a questionnaire was constructed, with twenty-eight questions, involving as many others adjectives that characterize a cognitive profile. In a first approximation, and taking only the descriptive statistics data into account, and taking only the sample data, there is a striking curiosity: the respondent students consider that the school made a visible and verifiable effort to correct the dominant profile. limbic pointing to a right cortical profile: intuition, entrepreneurship, vision.